Comparison of the Problem Based Learning and Inquiry Model with the Visual Media in Improving the Ability to Write Short Stories - Erna Marlina (Universitas Suryakanca, 2019)
This article will discuss the comparison of two learning models which are motivated by the ability to write short stories and the difficulties of students in expressing ideas and ideas in a short story. The method used in the research is experiment. Data collection techniques are carried out by tests, observations, and questionnaires. After posttest data analysis shows the value of sig (2-tailed) of 0.007 or 0.0035, meaning the value of sig (0.007) <a (0.05) H0 is rejected and Ha is accepted, at a significance level of 5% the average posttest score the experiment was 79.35 and the control class was 70.97. This means that the ability to write short stories of experimental class students who use the problem based learning model with visual media is better than the control class that uses the inquiry model with visual media. Keywords: problem based learning, writing, short stories, inquiry, visual media models